Erratum to: Quantifying the Visual Experience of Three-dimensional Built Environments [Journal of Asian Architecture and Building Engineering, Vol. 17 (2018), No.1, pp.117-124] - Dongkuk Chang; Joohee Park (Journal of Asian Architecture and Building Engineering, 2018)
Wrong: Acknowledgement This work was supported by the Korea Research Foundation Grant funded by the Korean Government (2015R1D1A1A01059898). Correct: Acknowledgement This study was supported by research fund from Chosun University, 2014.